The Effect of Price Changes in Luxury Goods - Vanessa Theiss; Laura Noll (Marketing Review St.Gallen, 2022)
During the COVID-19 crisis, luxury brands responded differently to sales shortfalls: some raised prices while others offered discounts. As research on the effect of price changes in luxury is scarce, a qualitative study was conducted to understand luxury consumers' responses to price changes, provide managerial implications, and extend existing literature.
Keywords: 650